Evaluating Mine Land Reclamation Policy In Indonesia: The Case Study Of East Kalimantan Province - Nadar, Sonny Widyagara; Supriyono, Bambang; Nuh, Muhammad; Jones, Thomas Edward (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2018)
The focus of this research is evaluating the mine land reclamation policy in East Kalimantan based on framework developed by Europe Environmental Agency (EEA). Using the reclamation rate as main indicator, the results show that there was no significant increase in reclamation rate after the regulation was issued (2017) compared to the pre-regulation era (2013). In fact the reclamation ratio of disturbed land actually decreased from 67.91% to 62.98% while the revegetation ratio to disturbed land increased slightly from 42.55% to 43.29%, showing that further research and an action plan is needed.